Anatomic crown length and mesio-distal width of maxillary central incisor teeth in Bangladeshi population - Md Mahfuz Hossain; Mushfiq Hassan Shaikh; Md Mahfuzur Raihan; Md Asif Iqbal Khan (Update Dental College, 2013)
Background : Dimensions of teeth have been an excellent tool for determining clinically relevant aspects of dental aesthetics. Especially, the anterior teeth crown height and their mesio-distal widths are very important, because of their strategic anatomical position of being in the centre and in the front of the upper jaw. Objectives : The presented study was aimed to find the nominative data of the average anatomic crown height and mesio-distal width of maxillary central incisors of Bangladeshi population irrespective of age and sex. Methods : This observational study was carried out at Update dental college & Hospital. 110 typical extracted human maxillary central incisor teeth were collected randomly from the Oral Anatomy and Physiology Department of Update dental college and Sapporo dental college. Results : In this study it shows that maxillary central incisors average crown length is between  7.25 11.75 mm and the mean crown length is 10.37(SD±0.90) mm. The average mesio-distal width is between 9.00 13.00 mm and the mean mesio-distal width  is 8.51 (SD±0.62) mm. Conclusions : Apart from other specific and objective parameters related to dental aesthetics, these values of mesio-distal width and the length of the maxillary central incisors mentioned in this study will serve as guidelines for the diagnosis and treatment planning, especially in restorative dentistry, orthodontics and periodontal surgeries. DOI: http://dx.doi.org/10.3329/updcj.v2i1.13954 Update Dent. Coll. j: 2012; 2 (1): 08-13